Absence of resting cardiovascular dysfunction in middle-aged endurance-trained athletes with exaggerated exercise blood pressure responses. Issue 8 (August 2017) - Currie, Katharine D.; Sless, Ryan T.; Notarius, Catherine F.; Thomas, Scott G.; Goodman, Jack M.
Abstract : Objective: Untrained individuals with exaggerated blood pressure (EBP) responses to graded exercise testing are characterized as having resting dysfunction of the sympathetic and cardiovascular systems. The purpose of this study was to determine the resting cardiovascular state of endurance-trained individuals with EBP through a comparison of normotensive athletes with and without EBP. Methods: EBP was defined as a maximal systolic blood pressure (SBP) at least 190 mmHg and at least 210 mmHg for women and men respectively, in response to a graded exercise test. Twenty-two life-long endurance-trained athletes (56 ± 5 years, 16 men) with EBP (EBP+) and 11 age and sex-matched athletes (55 ± 5 years, eight men) without EBP (EBP−) participated in the study. Sympathetic reactivity was assessed using BP responses to a cold pressor test, isometric handgrip exercise, and postexercise muscle ischemia. Resting left ventricular structure and function was assessed using two-dimensional echocardiography, whereas central arterial stiffness was assessed using carotid-to-femoral pulse wave velocity. Calf vascular conductance was measured at rest and peak postexercise using strain-gauge plethysmography. Results: All sympathetic reactivity, left ventricular, and arterial stiffness indices were similar between groups. There was no between-group difference in resting vascular conductance, whereas peak vascular conductance was higher in EBP+ relative to EBP− (1.81 ± 0.65 vs. 1.45 ± 0.32 ml/100 ml/min/mmHg, P  < 0.05). Conclusion: Findings from this study suggest that athletes with EBP do not display the resting cardiovascular state typically observed in untrained individuals with EBP. This response in athletes, therefore, is likely a compensatory mechanism to satisfy peripheral blood-flow demands rather than indicative of latent dysfunction.